Establishing biotic stress tolerance of maize (Zea mays L.) by measuring hydroxamic acid contents - Makleit, Péter; Frommer, Dóra; Veres, Szilvia (Acta Agraria Debreceniensis, 2018)
Cyclic hydroxamic acids are the most considerable secondary metabolites in grasses and their main task is to protect these species from pathogens and pests. The cyclic hydroxamic acid content and common smut susceptibility were examined in our experiments. 27 maize hybrids were used for experimental plants in a climate room, where the plants were grown on a nutrient solution. An infiltration method was used for the inoculation of the plants. The total quantity of cyclic hydroxamic acids was determined and the ratio of infected plants and the ratio of inhibition was determined, too. Based on our results, on the basis of all hybrids’ data, the total hydroxamic acid content of the infected plants was higher than in the control. On the level of individual hybrids, only 9 of them had higher cyclic hydroxamic acid content in the case of infection. Increase in cyclic hydroxamic content induced by the fungus in this case is a tool for the fungus to suppress other pathogens and pests. Amongst the hybrids’ cyclic hydroxamic acid contents, significant differences were detected in the control and in the infected treatment, too. The so-called “sweetcorn” hybrids showed high level of cyclic hydroxamic acid content. According to the differences amongst hybrids, homogenous groups were created which groups differed in the case of control and infected treatment, because of the difference in increase of cyclic hydroxamic acid content. The examined hybrids showed different levels of infection and different rate of growth inhibition for the effect of inoculation. According to the infection caused damage hybrids were ranked. Infection caused notable damage for hybrids Prelude, Desszert 73, DKC5276 and DK440.